Sap Business One Implementation Using the Kaizen Methodology Implementation of sap Business One Using the Kaizen Methodology in Mypes in the Automotive Sector. - Montero Zúñiga, Evelyn Trinidad (2020)
Companies require continuous improvement for the purpose of achieving competitiveness as a result of globalization in business that advances by leaps and bounds, leading us to streamline accounting and financial processes to obtain information in real time and make decisions in order to increase the productivity, equity and control of operations, achieving the positioning of the company. This is an applied research with an experimental design. It is based on the implementation of SAP BUSINESS ONE (Systems, Applications and Products in Data Processing) and the use of the Kaizen methodology in the different processes and operations carried out by companies in the automotive sector in the activities of sale and maintenance of new vehicles. The implementation and adaptation was executed in a period of one year, it was carried out in two stages, in the first one the information of the accounting system, the processes used, volume of operations, work team, current technology and ways of thinking of all were analyzed Company employees. In the second stage, the information obtained allows me to set the objectives of the implementation that is intended to be achieved. In the third stage, the interpretation and statistical analysis of the results obtained revealed that the accounting implementation of SAP BUSINESS ONE using the Kaizen methodology was satisfactory, which is expanded and demonstrated in the section on development, analysis, results and Conclusions.